HUBUNGAN KARAKTERISTIK SEDIMEN DENGAN HABITAT PENELURAN PENYU DI PANTAI TIRAM, PANTAI KARAMBIA AMPEK, DAN PANTAI GOSONG KABUPATEN PADANG PARIAMAN PROVINSI SUMATERA BARAT - Rahmi Relva; Rifardi Rifardi; Elizal Elizal (Berkala Perikanan Terubuk, 2020)
This research was conducted on 27 April-30 May 2019 at Tiram Beach, Karambia Ampek Beach and Gosong Beach, Padang Pariaman Regency, West Sumatra Province. This study aims to determine the relationship between sediment grain size and the number of turtle eggs. The method used in this research is purposive sampling. The sampling location is divided into 3 stations, each station is divided into 5 sampling points in order to obtain 15 sampling points, of which the fifteen sampling points are the usual nesting sites for turtles. Sediment samples were taken approximately 500 grams, put in a plastic bag, then labeled and then the sample was taken to the laboratory for analysis. The procedure for analyzing the sediment grains for sand and gravel fractions used the wet sieving method, for the sludge fraction was analyzed using the pipette method. The results from the wet sieving method and the pipette method were combined and the mean size (Mz) was obtained. Measurement data were analyzed using linear regression analysis, then correlation and regression analysis to determine the form of the relationship and the strength of the relationship between two or more variables. Sea turtles will lay eggs, namely the mean size ranges from 1.13-1.8 Ø. The coefficient of determination (R2) = 0.53 and the correlation coefficient r = 0.73. This means that the coefficient of determination shows the average diameter (mean size) affects 53% of the number of turtle eggs, while the other 47% is influenced by other factors, for example vegetation around the coast..